Use of IoT Tools to Support the Decision-making Process - Tóth, Mihály; Felföldi, János; Szilágyi, Róbert (International Journal of Engineering and Management Sciences, 2018)
Nowadays sensor networks and other systems, based on the IoT concept demonstrate the benefits of their usage, which includes the support of the decision-making process, therefore achieving an optimal result in the context of more and more fields. In this experiment, an additional sensor network has been developed based on a modular system derived from a previous development by means of a target-specific modification of the required modules to measure environmental data in a drying chamber used in food industry. The main objectives include the development of the device, the verification of the measurements of the factory-built device, providing an interface, which is able access the measurement data and after gathering experience from the usage, further developing the system and extending the functionality of the web application. The built-in data acquisition and control system stores the data of the measurements in the form of text files, while our additional data acquisition and control system uses a unified measurement database to store the data. According to the structure, a task-specific application has been developed in order to unify the two sources. Analysis of collected data was performed after running the ETL (extract, transform, load) algorithm converting the transaction-oriented database. The experiment shows so far the benefits of the multi-point measurements by a significant difference between the measured values, so we certainly consider further developments.